Estudos do uso de cistatinas visando a resistência à Diaphorina citri, inseto vetor da doença Huanglongbing (HLB), via CTV (Vírus da Tristeza dos Citros) na planta, e ensaios de interação patógeno-vetor com ênfase nas catepsinas B e L-like - Rocha, Sâmara Vieira (2024)
Brazilian citrus farming is one of the most important agricultural activities for the national economy, with Brazil being the world's leading producer of oranges and the largest exporter of concentrated and frozen citrus juice. Citrus groves, however, are constantly suffering from various phytosanitary problems, especially Huanglongbing (HLB), which has caused serious damage to citrus farming, since contaminated plants have smaller fruit, a higher degree of acidity, and a lower percentage of juice. The disease is mainly associated with the presence of the bacterium Candidatus Liberibacter asiaticus (CLas), which colonizes the phloem vessels and is transmitted to citrus plants by the psyllid Diaphorina citri. In the absence of strategies to control the CLas bacterium, the emphasis has been on controlling D. citri. Therefore, this study aimed to use a vector based on the Citrus Tristeza Virus (CTV) to overexpress the cystatins CclemCPI-1 and CsinCPI-2, to inhibit target peptidases in the D. citri psyllid. In addition, studies were carried out to understand the localization and gene and protein expression of D. citri cysteine peptidases in the presence or absence of CLas bacteria. Feeding bioassays were carried out with the psyllids using an artificial diet containing the recombinant citrus cystatins and were tested at three stages of D. citri development: egg, nymph and adult, in order to investigate the result of protein interactions (cystatins-peptidases) at different stages of development, as well as in the presence or absence of the bacterium associated with HLB. As for the results obtained, in citrus plants infected with the CTV vector, systemic infection was verified and the presence of the CTV-cystatins construct was confirmed. In the biological tests carried out with the CTV-cystatin plants, D. citri insects were confined, but the plants overexpressing the cystatins were not effective in reducing the viability/quantity of D. citri eggs and nymphs, which requires further investigation and repetition of the test adopted in this work. However, the importance of the psyllid's target peptidases was confirmed, especially in the presence of the CLas bacterium, which indicates their participation in the insect's defense responses. However, the presence of the bacterium is supposed to be a limiting factor for the efficacy of the cystatins, where populations free of the bacterium show a greater population reduction concerning the effect of the inhibiting protein when compared to insects contaminated by the bacterium. As for the developmental stages evaluated, the nymphs proved to be more susceptible to cystatin-mediated inhibition, with this stage being more effective for controlling the insect when using the recombinant proteins compared to the adult stage. A test carried out during the hatching of D. citri eggs in an artificial medium containing the cystatin CsinCPI-2 proved promising since the cystatin present in the artificial diet was supposedly able to interfere with the emergence of first-stage nymphs by reducing the hatching of the insect's eggs by 53.8%. These results require further investigation. Nevertheless, the use of cystatins to control D. citri is still highly promising and it is hoped that soon they will effectively form part of the establishment of citrus crops resistant to the HLB vector, as an effective but sustainable management strategy.